The effect of green finance on the transformation and upgrading of manufacturing industries in the Yangtze River economic belt of China - Sun, Yanbing; Zhong, Hui; Wang, Yuning; Pan, Yuhan; Tang, Decai (Frontiers in Environmental Science, 2024)
China's manufacturing sector is a cornerstone of its industrial system. However, some parts of China are dominated by heavy chemicals, which leads to severe environmental pollution. The emergence of green finance (GF) can influence social capital to gradually withdraw from companies that emit pollution and increase investment in environmentally friendly ones. This paper selects the data related to GF and the manufacturing industry (MI) from 2011 to 2020 by exploring the effect of GF on the transformation and upgrading of manufacturing industries (MIU) through literature analysis and the Spatial Durbin model. The results demonstrate that GF positively influences the promotion of MIU, whereas MIU has a good spatial spillover effect. The results of this regression remain robust after a series of tests. This research suggests that the government and enterprises should pay attention to GF and encourage more enterprises to take the initiative to adjust the industrial direction and achieve a clean upgrade in manufacturing.